2017
DOI: 10.1074/jbc.m117.786442
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of mitochondrial electron transport chain function potentiates the pro-apoptotic effects of MAPK inhibition

Abstract: The mitochondrial network is a major site of ATP production through the coupled integration of the electron transport chain (ETC) with oxidative phosphorylation. In melanoma arising from the V600E mutation in the kinase v-RAF murine sarcoma viral oncogene homolog B (BRAF), oncogenic signaling enhances glucose-dependent metabolism while reducing mitochondrial ATP production. Likewise, when BRAF is pharmacologically inhibited by targeted therapies ( PLX-4032/vemurafenib), glucose metabolism is reduced, and cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 55 publications
(79 reference statements)
2
60
0
1
Order By: Relevance
“…Another study demonstrated a potent antitumor effect of honokiol bis‐dichloroacetate in vemurafenib‐resistant melanoma in vivo . Consistently, a recent study showed a synergistic effect of honokiol and MAPK inhibitor in BRAFmt melanoma cells by disrupting mitochondrial electron transport chain . Since magnolol is structurally similar to honokiol, it is expected to have a similar effect on the BRAF inhibitor resistance melanoma cells; however, this requires further investigation.…”
Section: Discussionmentioning
confidence: 75%
“…Another study demonstrated a potent antitumor effect of honokiol bis‐dichloroacetate in vemurafenib‐resistant melanoma in vivo . Consistently, a recent study showed a synergistic effect of honokiol and MAPK inhibitor in BRAFmt melanoma cells by disrupting mitochondrial electron transport chain . Since magnolol is structurally similar to honokiol, it is expected to have a similar effect on the BRAF inhibitor resistance melanoma cells; however, this requires further investigation.…”
Section: Discussionmentioning
confidence: 75%
“…We have shown that PEITC is able to resensitize to vemurafenib BRAFi-resistant melanoma cell lines confirming the important role of glutathione in their survival. But PEITC is also able to induce disruption of the mitochondrial electron transport complex I and to inhibit mitochondrial respiration in some cancer cells lines as leukemia cells 27 , thereby by this mechanism it could also increase cytotoxicity of BRAFi as seen with other complex I inhibitors metformin or phenformin 11 , 28 . To inhibit GSH metabolism, we have also used sulfasalazine, an xCT inhibitor; we found that this drug delay in vitro the growth of BRAFi-resistant melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Higher supplement of these redox proteins can potentially contribute to protective effect of MSCs, particularly enhancing the utilization of ROS in damaged tissues and protecting membrane integrity. It was shown that disintegration of respiratory chain or its functional deficiency play role in both, p53 and MAPK apoptosis signaling pathways [27,28].…”
Section: Discussionmentioning
confidence: 99%